Price, Atmosphere, and Service Quality on Customer Loyalty - Rukaiyah, St.; Sultan, Sultan; Rosanti, Novita (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2026)
This study aimed to analyze the influence of price, atmosphere, and service quality on customer loyalty at SS Coffee Space in Makassar. A quantitative research design was employed, using a survey to collect primary data. Respondents were selected using purposive sampling based on the criteria of having visited the establishment more than twice. Data were analyzed using Partial Least Squares - Structural Equation Modeling to test the research hypotheses. The results revealed that price, atmosphere, and service quality each had a significant positive impact on customer loyalty. Among the factors examined, service quality was identified as the most dominant driver of consumer commitment. The model demonstrated substantial explanatory power, suggesting that the combination of fair pricing, an aesthetic environment, and excellent service effectively explained the variance in loyalty. These findings indicate that while price and environment are vital, service excellence is the primary factor for customer retention. Management should prioritize continuous service enhancement to maintain a competitive advantage.